Lower prevalence of protective antibodies for 2015/2016 influenza A(H1)pdm circulating strains comparing to seroprevalence for 2009 influenza A(H1)pdm virus - Guiomar, Raquel (2017)
Background: Since 2009, influenza A(H1)pdm09 is circulating in the human population infecting in different ways specific age groups. The study aims to assess the seroprotection for A/California /07/2009 vaccine strain and evaluate the seroprotection for the circulating A(H1)pdm09 strains (clade 6B) in the Portuguese population. Seroepidemiological data can determine the vulnerable populations to disease and support intervention and action regarding vaccination programmes and other preventive measures, particularly in high-risk groups. Methods: To study influenza immunity a non-probabilistic sample was used. Samples were collected from people attending to hospital laboratories (n=13) for other reasons aside from influenza infection. We developed a cross-sectional study based on a convenience sample of 734 sera collected during July 2016, from all age groups (0–4; 5–14; 15–44; 45-64 and ≥65 years old), both genders, covering mainland and Atlantic islands. Sera were randomly selected. All samples were anonymized and recorded data: district residence/sample collection, gender and age. Antibody titers to A(H1)pdm09 virus strains [A/California /07/2009 and A/Lisboa/58/2015 (clade 6B)] were assessed by hemagglutination inhibition (HI) assay. HI titer>40 were considered protective. Seroprevalence estimates, overall and by age group, were calculated with 95% confidence intervals (95% CI). The HA1 subunit of the hemagglutinin gene from A(H1)pdm09 viruses used in HI were sequenced. Results: In July 2016, the prevalence of protective antibodies for influenza A/California/07/2009 was 38% (95% CI: 34–41) and for A/Lisboa /58/2015 was 23% (95% CI: 21–27). Highest seroprevalence was observed in 5-14 age group for both strains, 55% (95% CI: 47–63) for A/California/07/2009 and 42% (95% CI: 35–50) for A/Lisboa/58/2015. The lowest seroprevalences were detected in the 65+ age group for A/California/07/2009 (28%; 95% CI: 22–36) and in the 45-64 for the A/Lisboa /58/2015 (9%; 95% CI: 6-15). Was observed a reduced prevalence of protective antibodies for A/Lisboa /58/2015 for all age groups, although a higher decrease was seen in the adults 45-64 years old (24% drop in seroprevalence). The influenza A/Lisboa/58/2015 presented four amino acid substitutions in antigenic sites: S162N e K163Q (Sa), S185T (Sb) and S203T (Ca1), belonging to 6B.1clade. Conclusions: Although 38% of study population have demonstrated to have seroprotection for A(H1)pdm09 vaccine strain this could not represent seroprotection to the currently circulating A(H1)pdm09 strains. Individuals in the age group of 45-64 years old are more susceptible to infection by currently circulating influenza A(H1)pdm09 viruses. The presence of K163Q (Sa), S185T (Sb) substitutions are likely to be involved in antigenic drift, as previously described, allowing the virus to escape from immune response namely the one that could be induced by the vaccine. In future this event should be closely monitored, although WHO recommended a new A(H1)pdm09 strain to be included in the next season flu vaccine.